Development of Maria Montessori’s Ideas in National Educational Thought at the Beginning of the ХХ Century - Kushnir, Valentina (Pedagogical Discourse, 2017)
Italian doctor, psychologist and educator Maria Montessori (1870 - 1952) has developed and implemented a practical method of education and training of children 3 to 9 years. It is based on the creation of a natural environment for the child’s expression and free development of his personality. Excluding any violence and pressure. Search for alternative models of education has led to interest in Ukrainian teachers Montessori method, which has gained worldwide recognition. In tsarist Ukrainian lands was not kindergarten, which would work on the system Montessori. Montessori method itself was widely known and actively discussed by the Ukrainian teachers. Appreciating method M.Montessori Ukrainian teachers did not consider it universal, it stressed the need to adapt to the realities of Ukrainian kindergartens, national characteristics, mentality and traditions. Key words: Montessori method, free education, S.Rusova, N.Lubenets, K.Mayevska.